Timing and evolution of multiple Paleoproterozoic magmatic arcs in the Tapajos Domain, Amazon Craton: constraints from SHRIMP and TIMS zircon, baddeleyite and titanite U-Pb geochronology - Santos, J.; Van Breemen, O.; Groves, D.; Hartmann, L.; Almeida, M.; McNaughton, Neal; Fletcher, Ian (Elsevier Science BV, 2004)
Knowledge of the geotectonic evolution of the Tapajos Domain of the Tapajos-Parima Orogen is of major significance in the Amazon Craton, for two reasons: first, the domain lies between the Archean Central Amazon Province to the east-northeast andthe Paleo-Mesoproterozoic Juruena Province (1820-1520 Ma) to the southwest and, second, it has produced a large proportion of Brazilian gold in the last century. Geological mapping, integrated with U-Pb zircon, baddeleyite and titanite SHRIMP and TIMS geochronology, shows that the Tapajos Domain is a complex array of plutonic and volcanic rock associations formed during two main events: the Tapajos-Parima Orogen (2040-1880 Ma) and a later post-orogenic period (1870-1760 Ma). Whole-rock and zircon geochemistry help discriminate both the more primitive from the more evolved orogenic rocks and the anorogenic rocks from the arc-related magmatism. In contrast with previous model, whereby the Orosirian Tapajos-Parima Orogenwas interpreted to have resulted from one orogeny involving three magmatic arcs, this new interpretation shows that the orogen developed during two distinct orogenies and incorporates five magmatic arcs. The two orogenies, Mundurucus (2040-1957 Ma) and Tropas (1906-1886 Ma) are separated by a hiatus of about 50 million years. The Mundurucus Orogeny started with island arc magmatism (banded tonalite, meta-basalt and meta-andesite, Cui-Cui Complex; 2040-1998 Ma) and turbiditic sedimentation in back-arcor trench basins (Jacareacanga Group) followed by the formation of two Andean-type continental arcs composed of syeno- and monzogranites and felsic to intermediate volcanic rocks (Jamanxim; 2000-1986 Ma; Creporizao, 1980-1957 Ma).After a hiatus of about 50 million years, the Tropas Orogeny also started with island arc magmatism (Tropas Suite; 1906-1886 Ma), again followed by formation of a third continental arc (Parauari Suite). Contrary to previous interpretations, which included all felsic to intermediate volcanic rocks from the Tapajos Domain in the Iriri Group (1.87 Ga), we now recognize older (2.02-1.88 Ga) orogenic calc-alkaline volcanic rocks in four orogenic arcs. The post-orogenic Uatum magmatism (Maloquinha Intrusive Suite of granitic rocks and Iriri Group of volcanic rocks) took place at ~1870 Ma, with another, much younger anorogenic magmatic event represented by the Porquinho Granite (1786 14 Ma) correlated to the Teles Pires Suite. Similarly, some of the intrusive post-orogenic granitic rocks are interpreted to be related to the younger Teles Pires Suite rather than to the Maloquinha Suite. Archean ages on inherited zircon, together with Sm-Nd data, provide strong evidence that the post-orogenic rocks were derived from continental Archean crust, possibly from the Central Amazon Province to the east.